FACTORS PREDISPOSING TO THE DEVELOPMENT OF CONSTIPATION IN CHILDREN FROM 4 TO 18 YEARS IN THE BUKHARA - Khamraeva Dilnoza Razzakovna (Scholar Express Journals, 2024)
The article examines possible predisposing factors for the development of constipation in children and discusses common causes and complications of constipation in children. The currently relevant causes leading to the development of constipation in children are considered, the complaints and observations of parents set out in a questionnaire compiled to identify constipation in children in the practice of a pediatrician are taken into account.
Keywords: children; gastrointestinal tract; constipation